FINANCIAL RESOURCES OF THE TREASURY SYSTEM AND ISSUES OF THEIR MANAGEMENT - Shaxlo Shodmonkulova Olimjon qizi (Zeta Repository, 2023)
In modern economic processes , views about the importance of the treasury system of the country, the budget execution of related bodies and the socio economic status of the country's population, some suggestions and opinions arising from the study of the works of foreign scientists in the field are the main content of this article.